POTENSI NITRIFIKASI OLEH BAKTERI YANG TERDAPAT DI LAUT ALIRAN KALI PLUMBON, LAUT ALIRAN KALI BANJIR KANAL BARAT DAN LAUT ALIRAN KALI BANJIR KANAL TIMUR - Nurlita Harsanti (Jurnal Teknik Lingkungan, 2012)
The difference of Nitrogen levels  in flowKali Plumbon sea,  West Banjir Kanal and East Banjir Kanal due to the difference of utilization area. Nitrogen can be degradated by nitrifying bacteria that has been able to adapt in high salinity water. In addition to minimizing nitrogen in the sea, the bacteria can be applied to the industrial wastes water that containing nitrogen with high salinity. The water samples from the three locations were put into the reactor and the ammonium was added as much as 25 mg-N / L, and then the nitrification process have to observed for 29 days. Nitrifying bacteria obtained from marine estuarine flow West Banjir Kanal  is the most optimal bacteria than the bacteria obtained Plumbon Kali and East Banjir Kanal sea,it’s because the bacteria obtained West Flood Canal was able to adapt to the conditions of high salinity, so that the bacteria can be able to degrade ammonium to nitrite and then to nitrate faster than the two other locations.